Conservative treatment of a Class I malocclusion with 12 mm overjet, overbite and severe mandibular crowding - Marcos Alan Vieira Bittencourt; Arthur Costa Rodrigues Farias; Marcelo de Castellucci e Barbosa (Dental Press Editora, 2012)
INTRODUCTION: A female patient aged 12 years and 2 months had molars and canines in Class II relationship, severe overjet (12 mm), deep overbite (100%), excessive retroclination and extrusion of the lower incisors, upper incisor proclination, with mild midline diastema. Both dental arches appeared constricted and a lower arch discrepancy of less than -6.5 mm. Facially, she had a significant upper incisors display at rest, interposition and eversion of the lower lip, acute nasolabial angle and convex profile. OBJECTIVE: To report a clinical case consisting of Angle Class I malocclusion with deep overbite and overjet in addition to severe crowding treated with a conservative approach. METHODS: Treatment consisted of slight retraction of the upper incisors and intrusion and protrusion of the lower incisors until all crowding was eliminated. RESULTS: Adequate overbite and overjet were achieved while maintaining the Angle Class I canine and molar relationships and coincident midlines. The facial features were improved, with the emergence of a slightly convex profile and lip competence, achieved through a slight retraction of the upper lip and protrusion of the lower lip, while improving the nasolabial and mentolabial sulcus. CONCLUSIONS: This conservative approach with no extractions proved effective and resulted in a significant improvement of the occlusal relationship as well as in the patient's dental and facial aesthetics. INTRODUÇÃO: paciente do sexo feminino, 12 anos e 2 meses de idade, apresentava molares em relação de chave de oclusão e caninos em relação de Classe II de Angle, sobressaliência acentuada (12mm), sobremordida profunda (100%), excessiva retroinclinação e extrusão dos incisivos inferiores e projeção dos superiores, com leves diastemas interincisais. Ambas as arcadas apresentavam-se constritas e a discrepância dentária inferior era de -6,5mm. Do ponto de vista facial, apresentava grande exposição dos incisivos superiores em repouso, interposição e eversão do lábio inferior, ângulo nasolabial agudo e perfil convexo. OBJETIVO: apresentar um caso clínico de má oclusão de Classe I com sobremordida e sobressaliência acentuadas, além de apinhamento severo, tratado com método conservador. MÉTODOS: o tratamento foi constituído de leve retração e intrusão dos incisivos superiores, e projeção dos incisivos inferiores até que todo o apinhamento fosse eliminado. RESULTADOS: obteve-se sobremordida e sobressaliência satisfatórias, manutenção da relação de chave de oclusão nos molares e obtenção dessa relação nos caninos e linhas médias coincidentes. As características faciais obtidas foram positivas, originando um perfil bastante agradável, com selamento labial passivo, promovido pela leve retração do lábio superior e projeção do lábio inferior, melhorando o ângulo nasolabial e o mentolabial. CONCLUSÃO: a abordagem conservadora, sem exodontias, mostrou-se efetiva e resultou em sensível melhora do relacionamento oclusal e da estética dentária e facial da paciente.